2018
DOI: 10.3847/1538-3881/aad22a
|View full text |Cite
|
Sign up to set email alerts
|

The Super Earth–Cold Jupiter Relations

Abstract: We report relations between inner (< 1 au) super Earths (planets with mass/radius between Earth and Neptune) and outer (> 1 au) giant planets (mass > 0.3 M J , or cold Jupiters) around Sun-like stars, based on data from both ground-based radial velocity (RV) observations and the Kepler mission. We find that cold Jupiters appear three times more often around hosts of super Earths than they do around field stars. Given the prevalence of the super Earth systems, their cold Jupiters can account for nearly all cold… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
133
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 129 publications
10
133
3
Order By: Relevance
“…8). This is in line with new observational data (Zhu & Wu 2018;Bryan et al 2018) and we discuss this more in section 6.…”
Section: Mass and Composition Of The Final Systemssupporting
confidence: 90%
See 1 more Smart Citation
“…8). This is in line with new observational data (Zhu & Wu 2018;Bryan et al 2018) and we discuss this more in section 6.…”
Section: Mass and Composition Of The Final Systemssupporting
confidence: 90%
“…Recent analysis of observational data of systems hosting super-Earths and gas giants suggest that most systems with cold Jupiter should also host interior super-Earths, especially if the metallicity is above solar (Zhu & Wu 2018;Bryan et al 2018), but also that the opposite could be true (Barbato et al 2018). Our simulations and those of our companion paper by Izidoro et al (2019) indicate that both outcomes are possible (see Fig.…”
Section: Initial Distribution Of Planetary Embryossupporting
confidence: 54%
“…Observations of exoplanets have reveled that close-in super-Earths are the most abundant type of planet within 1 AU (Mayor et al 2011;Mulders et al 2018;Zhu & Wu 2018). These super-Earths have typically masses of a few Earth masses and planets within the same system could be of similar size (Weiss et al 2018) and thus, presumably mass.…”
Section: Introductionmentioning
confidence: 99%
“…Recent observations have revealed that close-in super-Earths are very abundant and even more than 50% of all stars could host super-Earths (Mayor et al 2011;Mulders et al 2018;Zhu & Wu 2018). These super-Earth planets are typical of a few Earth masses and super-Earths within the same system are typical of similar size (Weiss et al 2018) and thus presumably mass, within a factor of two.…”
Section: Introductionmentioning
confidence: 99%